A randomised double-blind crossover study: once-daily low-dose prednisolone compared with thrice-daily hydrocortisone in adrenal insufficiency - Sirazum Choudhury; Katharine Lazarus; Angelica Sharma; Kavita Narula; Cara Go; Suzie Cro; Thilipan Thaventhiran; Bernard Khoo; Tricia Tan; Karim Meeran (Clinical Medicine, 2025)
Introduction: Thrice-daily hydrocortisone is the most popular glucocorticoid replacement regimen, followed by prednisolone, for adrenal insufficiency.1 Prednisolone offers a once-daily option, with a more physiological serum profile.2 Although both medications are endorsed by the Endocrine Society,3 prednisolone has previously been thought to have a worse side-effect profile,4 probably because it has previously been studied at supraphysiological doses of 7.5 mg. Recent evidence indicates these historic doses were excessive, because doses of 2–4 mg are more appropriate.5 This study compared conventional thrice-daily hydrocortisone regimens against once-daily low-dose prednisolone therapy. Materials and Methods: This was a double-blind, randomised, two-arm, two-period crossover study. Forty-six patients with adrenal insufficiency were recruited from endocrinology outpatient clinics. Half of the participants were randomised to either Arm 1: low-dose prednisolone in the first period, and half to Arm 2: thrice daily hydrocortisone in the first period (Fig 1). All participants received the alternative medication in the second period. Blinding was maintained using single tablets manufactured for the study. While on hydrocortisone, patients received 10/5/2.5 mg, in the morning, noon and afternoon, respectively. On prednisolone, they received low-dose prednisolone in the morning (2–5 mg), followed by matching placebo at noon and in the afternoon. Study visits were conducted in the morning and were stereotyped to reduce circadian effects. Anthropometric data, including weight, waist–hip circumferences, blood pressure and heart rate, were collected at Day 1 (baseline), 30 (interim) and 120 (endpoint) in both study periods. Blood was collected for biochemical cardiovascular and bone turnover markers. Quality of life was measured using validated questionnaires at each visit (SF-36 and Addisons Quality of Life (Addi-QoL)). Results and Discussion: Hydrocortisone was associated with an increase in weight of 1.87 Kg (p=0.002). Waist circumference showed a treatment difference of –2.26 cm (p=0.010) in favour of prednisolone. HbA1c was also significantly lower by –1.23 mmol/mol (p=0.001; Fig 2) with prednisolone. Bone resorption was monitored using urinary N-telopeptide, which was suppressed by –9.34 nmol/mmol (p=0.002) with prednisolone. Bone formation markers (procollagen 1 N-terminal propeptide and osteocalcin) were higher with hydrocortisone, with treatment differences of 13.8 ng/L (p<0.001) and 1.22 µg/L (p=0.035), respectively. There was no significant difference in blood pressure, high-sensitivity troponin and CRP. Data from the SF-36 survey and Addi-QoL questionnaire demonstrated that subjective health outcomes were unaffected by either hydrocortisone or prednisolone.Low-dose prednisolone was associated with weight loss and reductions in HbA1c. Although short-term markers were used, they are indicative of better cardiovascular outcomes with prednisolone. These data will help normalise the use of prednisolone in adrenal insufficiency, opening the gate to longer term studies. The underlying mechanism for these findings are likely related to multiple-dose regimens of hydrocortisone causing greater steroid exposure. Alternatively, once-daily dosing may be mimicking the normal diurnal rhythm of physiological cortisol secretion better than thrice-daily hydrocortisone.6 Conclusion: Once-daily low-dose prednisolone is a safe alternative to standard-regimen hydrocortisone and may provide better cardiovascular outcomes without compromising subjective health. Future studies are needed to explore longer term outcomes, such as bone mineral density and real-world mortality.